A study on factor that affecting prices of corporate bond / Muhamad Azri Anuar - Anuar, Muhamad Azri (Faculty of Business and Management, 2012)
This paper is study and analyzes how external variables of the economy affect the corporate bond price. Researcher analyze three independent variable involved in fluctuation of corporate bond price where is interest rate, foreign exchange rate and inflation rate. Researcher collected the data more in secondary resources. Data obtained will analyzed by researcher test the hypotheses and build conclusion also recommendation. This study would use the aid of software such as Microsoft Excel and EVIEWS 7 to analyze and process the data. In this paper, Single Linear Regression approach was used to determine the impact of inflation, interest and exchange rate changes to the corporate bond price in Bloomberg (Europe) market. This research builds to study and analyze the trend of bond price on Bloomberg indices, for the period July 2010 until November 2010. Monthly data were used for the analysis. The result shows that inflation and exchange rate no significant relationship between the variables but only Interest rate have a significant relationship to corporate bond price and inverse relationship existed. These results are useful for students, other researchers and university.